Sejarah Pemikiran Ekonomi Islam: Aktivitas dan Etika Perdagangan pada Masa Rasulullah - Batubara, Maryam; Khairani, Devia Astry; Ujung, Siti Khoiriyah Karina; Febrianti, Yulia; Lubis, Husnul Khotima (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Islamic Economic History thought has the potential to become a bridge between earlier and later times, reshaping the latter to counteract the emergence of Islam and transform economics into a distinct academic discipline. Concerning the economic issues.The writings of early fiqh scholars teaching the Qur'an regarding existing economic problems were few and specific. This rope can be seen in the writings of early fiqh scholars teaching the Qur'an. The Qur'an mostly provides guidelines and prohibits the use of logic.This is what encouraged the emergence of virtuous scholars who work to organize committees to address new legal issues and develop legal logic (ushûl al-Fiqh) that can be applied to various segments of society.In addressing several issues, including economics, the scholars emphasize the Qur'an and the Sunnah of Prophet Muhammad as authoritative sources, along with various misdeeds committed by the followers of the prophet who arrived secretly. However, if they do not understand the legal implications in these summaries, they will apply analogies (qiyâs) and other derivation procedures to apply Sharia to new situations. Whenever a day passes, a number of fiqh mazhabs appear.